2020
DOI: 10.2116/analsci.19sbp06
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Shirasu-balloons Surface for Removal of Cadmium Ions from Contaminated Soil

Abstract: Microspheres of aluminosilicate glass from volcanic sediment, whose surface was modified with functional groups, Shirasu-balloons (SB) were investigated as an adsorbent to remove cadmium ion from the contaminated soil. The introduction of thiol group (-SH) on the surface of SB enabled to adsorb cadmium ion, meanwhile the introduction of an alkyl group (-ODS) made the surface of SB hydrophobic, consequently increased the mechanical strength of SB. Those adsorbents could float up on the water surface after adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that the Shirasu‐based materials can adsorb ions [44–46] and compounds [47,48] . On the other hands, surface modification of Shirasu‐based materials were effective ways to improve their adsorption capacities of the chemical species [44,45,47,48] . We have also identified the effect of surface modification of a Shirasu‐based material via various pretreatment procedures (solution treatment and calcination) on improving its surface acidity and promoting a chemical reaction in the presence of acids [49] .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been reported that the Shirasu‐based materials can adsorb ions [44–46] and compounds [47,48] . On the other hands, surface modification of Shirasu‐based materials were effective ways to improve their adsorption capacities of the chemical species [44,45,47,48] . We have also identified the effect of surface modification of a Shirasu‐based material via various pretreatment procedures (solution treatment and calcination) on improving its surface acidity and promoting a chemical reaction in the presence of acids [49] .…”
Section: Introductionmentioning
confidence: 92%
“…[47,48] On the other hands, surface modification of Shirasu-based materials were effective ways to improve their adsorption capacities of the chemical species. [44,45,47,48] We have also identified the effect of surface modification of a Shirasu-based material via various pretreatment procedures (solution treatment and calcination) on improving its surface acidity and promoting a chemical reaction in the presence of acids. [49] While, it has been reported that adsorption capacities of carbon dioxide of zeolites were improved by increasing their acidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation